Downward Spiral of Bullying: Victimization Timeline From Former Victims’ Perspective - Ptasińska-Wójcik, Małgorzata (Journal of interpersonal violence, 2022)
The present study aimed to investigate how those who had been chronic victims of bullying perceive their bullying experience from their initial attacks to their bullying exit, how they understood processes and actions causing a situation to become progressively worse, and how they interpreted their own coping behaviors. Nine individuals who were victimized for at least 6 years were interviewed. The grounded theory approach was used to analyze the data, which generated a grounded theory of the downward spiral of bullying, demonstrating hidden aspects of bullying?the victim?s inner process as a response to external victimizing and accompanying events. The interdependence of those processes is presented in a timeline to show their cumulative nature as new vicious circles of bullying involving maladaptive coping strategies (e.g., self-blame), which form an overriding pattern of behavior that renders victims unable to break it even if they enter a new peer group. In terms of policy implications, the findings suggest the need to introduce school transition programs supporting school adaptation, identify chronic victims, and take every victimhood narrative seriously.